Photophysical, photochemical and photobiological properties of anthraquinones isolated from a phototoxic vegetal species: Heterophyllaea pustulata - Comini, Laura Raquel (2010)
Studies undertaken on isolated photosensitizing agents from Heterophyllaea pustulata, a photo-toxic plant, which natural habitat is the North-western part of Argentina, are presented here. The carried out work involved several steps that were initiated with the chemical-structural study of their most important secondary metabolites. As a result, three flavonoids, one iridoid glycoside (asperuloside) and ten aglycone anthraquinones were identified. Through the study of the photo-physical, photochemical and photobiological properties of the anthraquinone derivatives, we concluded that they show good photosensitizing (type I and type II) characteristics. The performed toxicological assays in vivo showed a direct cause-effect relation between these metabolites and the reported phototoxicity for H. pustulata. Finally, a few words about the potential application of these photsensitizing compounds as antibacterial agents will be given.